Exposure to endocrine disrupting chemicals among residents of a rural vegetarian/vegan community. (December 2016) - Tordjman, Karen; Grinshpan, Laura; Novack, Lena; Göen, Thomas; Segev, Dar; Beacher, Lisa; Stern, Naftali; Berman, Tamar
Abstract: Background & Aims: Endocrine-disrupting chemicals (EDCs) are increasingly thought to be involved in the rising prevalence of disorders such as obesity, diabetes, and some hormone-dependent cancers. Several lines of evidence have indicated that vegetarian and vegan diets may offer some protection from such diseases. We hypothesized that exposure to selected EDCs among residents of the unique vegetarian/vegan community of Amirim would be lower than what has recently been reported for the omnivorous population in the first Israel Biomonitoring Study (IBMS). Methods: We studied 42 Amirim residents (29 vegetarians/13 vegans; 24 women/18men, aged 50.7 ± 13.7 y). Subjects answered detailed lifestyle, and multipass, memory-based 24-hr dietary recall questionnaires. Concentrations of bisphenol A (BPA), 11 phthalate metabolites, and the isoflavone phytoestrogens (genistein and daidzein) were determined by GC or LC tandem mass-spectrometry on a spot urine sample. The results were compared to those obtained following the same methodology in the Jewish subgroup of the IBMS (n = 184). Results: While a vegetarian/vegan nutritional pattern had no effect on exposure to BPA, it seemed to confer a modest protection (~ 21%) from exposure to high molecular weight phthalates. Furthermore, the summed metabolites of the high molecular weight phthalate DiNP were 36% lower in vegans compared to vegetarians (P < 0.05). In contrast, Amirim residents exhibited a level of exposure to isoflavone phytoestrogens about an order of magnitude higher than in the IBMS (P < 0.001). Conclusions: In Israel, a country whose inhabitants demonstrate exposure to EDCs comparable to that of the US and Canada, a voluntary lifestyle of vegetarianism and preference for organic food has a modest, but possibly valuable, impact on exposure to phthalates, while it is associated with a very steep increase in the exposure to phytoestrogens. Major reduction in exposure to EDCs will require regulatory actions. Highlights: A vegetarian diet is thought to confer protection from non-transmissible diseases. A unique community of vegetarians was assessed for exposure to endocrine disruptors. Exposure to phthalates was 21% lower than in the general population. A vegetarian/vegan diet offered no protection from bisphenol A exposure. A voluntary dietary change does not appear to be a solution to global EDCs exposure.